Supracondylar periprosthetic femoral fractures following total knee arthroplasty: treatment with a retrograde intramedullary nail - Chettiar, K. (Springer-Verlag, 2008)
Total knee replacement surgery is occasionally complicated by a supracondylar periprosthetic fracture, and this presents a challenging problem in an often frail population. Multiple nonoperative and operative treatments have been described which have the aim of restoring the patient to their pre-injury status. This study retrospectively reviews the results of the largest series to date of 14 such fractures treated by retrograde intramedullary supracondylar nailing and is supportive of its continued use with good functional outcomes, low complication rates, and 100% fracture union.